Triallyl cyanurate copolymerization delivered nonflammable and fast ion conducting elastic polymer electrolytes. Issue 43 (14th October 2022) - Zhang, Dashan; Shi, Yongzheng; An, Junwei; Yang, Shubin; Li, Bin
Abstract : An elastic solid polymer electrolyte is developed based on the unique properties of triallyl cyanurate, which is beneficial for fast lithium-ion conduction and preventing the combustion of polymer electrolyte. Abstract : Although solid polymer electrolytes (SPEs) possess competitive advantages of excellent processability and good interfacial contact with electrodes over rigid and fragile inorganic solid electrolytes, the unsatisfactory ionic conductivities and undesired flammability issues still impede their practical applications. In this report, derived from the vulcanized nitrile butadiene rubber (v-NBR) matrix, a nonflammable, elastic, and fast lithium ion conducting SPE (v-NBR/TAC/IL) is developed via introducing the triallyl cyanurate crosslinking agent and an ionic liquid plasticizer. The abundant CC bonds and triazines in the triallyl cyanurate agent are utilized as vulcanization accelerators to cross link the NBR matrices and as flame retardants to inhibit the combustion of the electrolyte, respectively. Furthermore, the electronegative nitrogen atoms in triallyl cyanurate can help delocalizing lithium salts, facilitating the dissociation and transportation of lithium ions. Therefore, the resultant rubber-based polymer electrolyte exhibits excellent flame retardancy, good mechanical properties (0.58 MPa, 162% elongation) and high ionic conductivity (1.8 × 10 −4 S cm −1 at room temperature). Consequently, the lithium symmetrical battery with v-NBR/TAC/IL electrolyte exhibits a long plating/stripping cycling for up to 1500 h, and the full battery of Li|v-NBR/TAC/IL|LiFePO4 displays a high specific capacity of 132.6 mA h g −1 and a long cycling life over 250 cycles.